Biotic and abiotic factors shape the microbiota of wild‐caught populations of the arbovirus vector Culicoides imicola. Issue 6 (17th September 2018) - Díaz‐Sánchez, S.; Hernández‐Jarguín, A.; Torina, A.; Fernández de Mera, I. G.; Estrada‐Peña, A.; Villar, M.; La Russa, F.; Blanda, V.; Vicente, J.; Caracappa, S.; Gortazar, C.; de la Fuente, J.
Abstract: Biting midges of the genus Culicoides are known vectors of arboviruses affecting human and animal health. However, little is known about Culicoides imicola microbiota and its influence on this insect's biology. In this study, the impact of biotic and abiotic factors on C. imicola microbiota was characterized using shotgun‐metagenomic sequencing of whole‐body DNA samples. Wild‐caught C. imicola adult nulliparous females were sampled in two locations from Sicily, Italy. The climatic variables of temperature and soil moisture from both localities were recorded together with potential host bloodmeal sources. Shared core microbiome among C. imicola populations included Pseudomonas, Escherichia, Halomonas, Candidatus Zinderia, Propionibacterium, and Schizosaccharomyces . Specific and unique taxa were also found in C. imicola from each location, highlighting similarities and differences in microbiome composition between the two populations. DNA and protein identification showed differences in host preferences between the two populations, with Homo sapiens and Canis lupus familiaris L. being the preferred bloodmeal source in both locations. A principal component analysis showed that the combined effect of host preferences ( H. sapiens ) and local soil moisture factors shape the microbiome composition of wild‐caught populations of C. imicola . These results contribute to characterizing the role of the microbiome in insect adaptation and its utility in predicting geographic expansion of Culicoides species with potential implications for the control of vector‐borne diseases.